Optimization of Corona Ring for 230 kV Polymeric Insulator Using Numerical Method Combined with Statistical Approach and Different Optimization Techniques - Thapa, Saurav; Adhikari , Ananta; Adhikari, Rammani (Himalayan Journal of Applied Science and Engineering, 2025)
The key factor governing the long-term reliability of high-voltage composite insulators is electric field distribution. However, when exceeding thresholds and applied for long periods, electric field stresses under severe pollution conditions could lead to deterioration and degradation of the housing materials and consequently lead to failures of the composite insulators. High electric field stress near the energized end fitting results in a corona discharge, mainly leading to the composite insulator's aging. At the critical zone, the electric field strength can be lowered to an acceptable value by different approaches and among them installing a corona ring is considered an effective way. This research is intended to study the electric field distribution across clean and polluted insulator and to design optimized corona ring that improves the electric field stress near the triple junction point (i.e. junction between polymeric shed, surrounded air, and energized end fitting). Finite Element Method is combined with MATLAB in-order to obtain different critical electric field stress at triple junction point for different corona ring configuration. Based on the result from different configurations, optimization function is generated using statistical approach i.e. using MINITAB, which is then further optimized using different optimization techniques (Particle Swarm Optimization, fmincon and Runge Kutta Method). The optimized design parameters are validated with the implementation of the Finite Element Method for the clean and polluted (uniform and non-uniform) insulator resulting 58.852.% and 54.48% reduction of electric field stress for normal and non-uniform pollution condition compared to recommended corona ring.